2004
DOI: 10.1111/j.1460-9568.2004.03676.x
|View full text |Cite
|
Sign up to set email alerts
|

A disaccharide derived from chondroitin sulphate proteoglycan promotes central nervous system repair in rats and mice

Abstract: Chondroitin sulphate proteoglycan (CSPG) inhibits axonal regeneration in the central nervous system (CNS) and its local degradation promotes repair. We postulated that the enzymatic degradation of CSPG generates reparative products. Here we show that an enzymatic degradation product of CSPG, a specific disaccharide (CSPG-DS), promoted CNS recovery by modulating both neuronal and microglial behaviour. In neurons, acting via a mechanism that involves the PKCalpha and PYK2 intracellular signalling pathways, CSPG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 74 publications
(92 reference statements)
7
52
0
Order By: Relevance
“…Another possibility, however, is that the products of CSPG GAG degradation may enhance axon repair. This hypothesis has been supported by Rolls et al (2004), who demonstrated that GAG disaccharide units released from cABC-mediated CSPG GAG degradation could stimulate axon repair by promoting axon outgrowth, overcoming the effects of strong repulsive factors, and activating the neuroprotective phenotype of endogenous microglia. Therefore, cABC treatment might stimulate axon regeneration by releasing GAG disaccharides.…”
supporting
confidence: 48%
“…Another possibility, however, is that the products of CSPG GAG degradation may enhance axon repair. This hypothesis has been supported by Rolls et al (2004), who demonstrated that GAG disaccharide units released from cABC-mediated CSPG GAG degradation could stimulate axon repair by promoting axon outgrowth, overcoming the effects of strong repulsive factors, and activating the neuroprotective phenotype of endogenous microglia. Therefore, cABC treatment might stimulate axon regeneration by releasing GAG disaccharides.…”
supporting
confidence: 48%
“…Interestingly, functional recovery was not observed until at least 6 weeks post-SCI, probably because axons retracted from the lesion site after injury, and outgrowth was not initiated until CSPG digestion rendered the substrate permissive to axon growth. Moreover, the effects of chABC may partially be due to antiinflammatory and neuroprotective effects of the soluble disaccharidic end products of chABC-mediated digestion of CSPG (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…This enzymatic digestion results in the release of bound growth factors from chondroitin sulfate GAG chains [9] , and reduction of the glial scar neoepitopeinduced immune response [10] . Also, one of the digestion products, the chondroitin sulfate E-disaccharide, is growthpromoting [11] . The enzyme remains active in vivo for 10 days after injection.…”
Section: Introductionmentioning
confidence: 99%